The study of socio-economic impact on the project participants, perceptions and attitudes on SALCRA Bratak Oil Palm Estate, Bau project - Martin, Kusong (Universiti Malaysia Sarawak (UNIMAS), 2002)
The aim of this study was to find out the socio-economic impact of SALCRA Bratak project on the participants. The perception and attitude patterns of the participants towards SALCRA and the project were also evaluated.